Enhanced biodegradation of pyridine using sequencing batch biofilm reactor under intermittent micro-aerobic condition. Issue 8 (2nd April 2020) - Sun, Guoping; Wan, Junfeng; Sun, Yichen; Xie, Yunfei; Ren, Shengtao; Wang, Yan
ABSTRACT: A sequencing batch biofilm reactor under intermittent micro-aerobic or anaerobic conditions was investigated to remove pyridine at various concentrations from synthetic wastewater. The results showed that over 98% of pyridine (influent concentration ≤200 mg L −1 ) was degraded under intermittent micro-aerobic condition, while about 21% of pyridine was removed under anaerobic condition. Additionally, at least 60% of nitrogen located in the pyridine ring was transformed to ammonium. At the same time, the sulphate reduction was obviously inhibited under intermittent micro-aerobic conditions. The microscopic observation showed that abundant microorganisms were attached on the surface or inside of porous biocarriers under intermittent micro-aerobic conditions after a short-term period of operation. High-throughput sequencing analysis demonstrated that Azotobacter, Rhodobacteraceae and Tolumonas were the dominant species in the intermittent micro-aerobic system. The kinetic study at steady period showed that pyridine degradation was fitted well with the pseudo-first-order model ( R 2 > 0.96). The two possible intermediate products were identified and the possible biodegradation pathway of pyridine was proposed under micro-aerobic condition. GRAPHICAL ABSTRACT: